Automated essay scoring for Bangla - Mahjabin, Rubayet; Farzana, Shaoli; Zerin, Nishat; Chowdhury, Sameer Sadman; Hossain, Ishmam (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.